A Study on Cattle Feeding Practices and Habits of Cattle Enterprises in Central County of Ağrı Province - Abdulkerim Diler; Mete Yanar; Veysel Fatih Özdemir; Recep Aydın; Rıdvan Koçyiğit; Ahmet Yılmaz (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out in the central county of Ağrı Province in order to reveal the cattle feeding habits of cattle breeders. For this purpose, data were obtained by conducting a face-to-face survey with 400 dairy cattle owners of the enterprises in the county. According to the results obtained from this study, it was determined that 91.5% of the breeders produced their forage crops. It was also found out that barley, alfalfa, and sainfoin were the most produced plants in these enterprises. However, the production of the corn silage, which is an important source of roughage for dairy cattle, was performed at a very low level (1.2%). Dry hay (93.5%) took first place among the roughage sources used in these enterprises, and it was followed by alfalfa hay (61.5%) and wheat-barley straw (28.0%). Corn silage was used at a low level (7.8%) in the cattle enterprises. It was determined that cattle breeders in the central county of Ağrı province were deficient in terms of some information about cattle feeding practices. It was also demonstrated that it was necessary to increase the usage and production of corn silage as forage crops and to implement rational animal feeding practices in place of the old traditional animal feeding habits. Therefore, cattle breeders in the central county of Ağrı province should be involved in technical training programs about the cattle feeding and forage planting. As result of the courses given to the cattle breeders, their technical information about cattle nutrition and preparation of ration would be updated. For this purpose, it is also recommended that agricultural extension service should be boosted to increase the education level and awareness of the cattle breeders in the rural areas.